The structure of an AspRS–tRNA(Asp) complex reveals a tRNA-dependent control mechanism - Moulinier, L. (Oxford University Press, 2001)
The 2.6 Å resolution crystal structure of an inactive complex between yeast tRNA(Asp) and Escherichia coli aspartyl-tRNA synthetase reveals the molecular details of a tRNA-induced mechanism that controls the specificity of the reaction. The dimer is asymmetric, with only one of the two bound tRNAs entering the active site cleft of its subunit. However, the flipping loop, which controls the proper positioning of the amino acid substrate, acts as a lid and prevents the correct positioning of the terminal adenosine. The structure suggests that the acceptor stem regulates the loop movement through sugar phosphate backbone– protein interactions. Solution and cellular studies on mutant tRNAs confirm the crucial role of the tRNA three-dimensional structure versus a specific recognition of bases in the control mechanism.